A New Method for Measuring Glenoid Version on Standard Magnetic Resonance Imaging. (May 2020) - Maister, Nicholas J.; Hely, Andrew; Twycross, Liam G.; Gill, Stephen D.; Page, Richard S.
Background: The most effective method and modality for measuring glenoid version for different shoulder conditions is uncertain. Computed tomography (CT) imaging exposes the patient to radiation, and standard magnetic resonance imaging (MRI) does not consistently image the entire scapula. This study investigates the reliability of a new method for assessing glenoid version using routine shoulder MRI. Methods: MRI images of 20 patients undergoing arthroscopy for shoulder instability were independently assessed by 3 clinicians for osseous and chondrolabral glenoid version. To assess glenoid version, a line was drawn from medial corner of the glenoid body to midpoint of the glenoid face. A line perpendicular to this was the reference against which to measure glenoid version. Measurements were repeated after 3 months to assess intra- and interobserver reliability. Reliability was determined using intraclass correlation coefficients (ICCs). Results: Interclass correlation coefficients showed at least good reliability for most estimates of intraobserver reliability (ICC ≥ .66) and excellent reliability for most estimates of interobserver reliability (ICC ≥ .84), with the exception of some inferior glenoid measurements where ICC was poor (ICC ≤.41). Discussion: We propose that this new method of measuring glenoid on standard axial MRI can be used as a simple, practical, and reliable method in shoulder instability patients, which will reduce the requirement for CT in this group.